Review article: novel biomarkers in hepatitis B infection. Issue 5 (30th June 2022) - Lok, James; Dusheiko, Geoffrey; Carey, Ivana; Agarwal, Kosh
Summary: Background: Chronic hepatitis B remains a global health problem with an estimated 296 million people affected worldwide. Individuals are at risk of serious complications such as cirrhosis and hepatocellular carcinoma and accurately predicting these clinical endpoints has proven difficult. However, several viral biomarkers have recently been developed, including quantitative HBV surface antigen (qHBsAg), hepatitis B RNA (HBV RNA) and core‐related antigen (HBcrAg), and shown promise in a range of clinical settings. Aims: To critically appraise these novel biomarkers, exploring their potential uses, availability of assays and areas for future development. Methods: We performed a literature search of PubMed, identifying articles published in the field of hepatitis B biomarkers between 2010 and 2022. Results: Novel biomarkers such as HBcrAg, HBV RNA and qHBsAg may be useful in predicting treatment outcomes, stratifying the risk of future complications and estimating off‐treatment viral reactivation. Furthermore, HBV RNA and HBcrAg titres may accurately reflect cccDNA transcriptional activity, and this is particularly informative in the context of nucleoside analogue therapy. On a cautionary note, most studies have been performed in Caucasian or Asian populations, and methods for detecting HBV RNA lack standardisation. Conclusion: Novel viral biomarkers have the potential to provide additional insights into the natural history of infection and allow a more bespoke, cost‐effective framework of care. However, access remains limited, and further efforts are needed to validate their use in ethnically diverse populations, confirm predictive cut‐off values, and establish their role in the era of novel antiviral therapies. Abstract : Novel biomarkers in hepatitis B infection.